2011
DOI: 10.1029/2010jd014618
|View full text |Cite
|
Sign up to set email alerts
|

Computation of clear-air radar backscatter from numerical simulations of turbulence: 2. Backscatter moments throughout the lifecycle of a Kelvin-Helmholtz instability

Abstract: [1] Franke et al. (2011) describe a numerical simulation of the instability and turbulent breakdown of Kelvin-Helmholtz (KH) billows at a high Reynolds number, numerical assessment of radar backscatter, and accuracies of inferred Doppler spectral moments for one test volume. Those results suggest a potential for significant measurement biases for radars that obtain backscatter from refractive index fluctuations. We present in this paper the morphology of computed radar moments throughout the KH instability lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 78 publications
0
19
0
Order By: Relevance
“…Rapp and Lübken, 2004). Intensive modelling studies of turbulence generated at mesopause altitudes showed anisotropy of the turbulence fields and radar backscatter (Gibson-Wilde et al, 2000;Fritts et al, 2003Fritts et al, , 2009Fritts et al, , 2011. However, to our knowledge there is no quantitative estimation of aspect sensitivity for such turbulence so far (perhaps with the exception of Hocking and Hamza (1997) who analytically considered anisotropic turbulence due to wind-shear only).…”
Section: Discussionmentioning
confidence: 99%
“…Rapp and Lübken, 2004). Intensive modelling studies of turbulence generated at mesopause altitudes showed anisotropy of the turbulence fields and radar backscatter (Gibson-Wilde et al, 2000;Fritts et al, 2003Fritts et al, , 2009Fritts et al, , 2011. However, to our knowledge there is no quantitative estimation of aspect sensitivity for such turbulence so far (perhaps with the exception of Hocking and Hamza (1997) who analytically considered anisotropic turbulence due to wind-shear only).…”
Section: Discussionmentioning
confidence: 99%
“…Our initial high‐resolution numerical studies of KHI [ Werne and Fritts , , ; Fritts et al ., ; Werne et al ., ] employed a pseudo‐spectral DNS code that solves the nonlinear Navier‐Stokes equations subject to the Boussinesq approximation in a Cartesian domain to explore the dependence of these dynamics and effects for various environmental parameters. A LES extension of the DNS modeling capability allowing application to a higher Reynolds number was also employed to explore the nature and implications of radar backscatter from KHI structures in the atmosphere [ Franke et al ., ; Fritts et al ., , ]. Here we summarize these methods and illustrate some of the results that are pertinent to our application to KHI dynamics observed in NLC images.…”
Section: Numerical Modeling Of Khi and Representation Of Nlc Responsesmentioning
confidence: 99%
“…We note that M 2 UAV and M 2 radar agree well in the turbulent layer during UAV7 (descent). Radar echoes are now at a minimum, and this feature may indicate the late decay stage of turbulence (e.g., Fritts et al, 2011). 3. M 2 UAV ≤ M 2 radar in convective clouds.…”
Section: A Much More Complex Relationship Exists Betweenmentioning
confidence: 99%